The Peculiars - McQuerry, Maureen, 1955- (Amulet Books, 2012)
Eighteen-year-old Lena Mattacascar sets out for Scree, a weird place inhabited by Peculiars, seeking the father who left when she was young, but on the way she meets young librarian Jimson Quiggley and handsome marshall Thomas Saltre, who complicate her plans.